2008
DOI: 10.1136/oem.2007.037721
|View full text |Cite
|
Sign up to set email alerts
|

Mobile phone base stations and adverse health effects: phase 1 of a population-based, cross-sectional study in Germany

Abstract: A substantial proportion of the German population is concerned about adverse health effects caused by exposure from mobile phone base stations. The observed slightly higher prevalence of health complaints near base stations can not however be fully explained by attributions or concerns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
83
2
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(95 citation statements)
references
References 12 publications
3
83
2
3
Order By: Relevance
“…So far, no health effects could consistently be demonstrated below this level (Röösli et al 2010b). Nevertheless, there is some uncertainty about long term health effects at low exposure levels and minimizing exposure to RF-EMF has been recommended Blettner et al 2008;Neubauer et al 2007;WHO 2010) and many countries have thus introduced precautionary limits. Whether such measures are effective to reduce population exposure has not been evaluated so far.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, no health effects could consistently be demonstrated below this level (Röösli et al 2010b). Nevertheless, there is some uncertainty about long term health effects at low exposure levels and minimizing exposure to RF-EMF has been recommended Blettner et al 2008;Neubauer et al 2007;WHO 2010) and many countries have thus introduced precautionary limits. Whether such measures are effective to reduce population exposure has not been evaluated so far.…”
Section: Discussionmentioning
confidence: 99%
“…This growth and ubiquitous use of wireless technology in society has raised public concerns regarding potential adverse health effects from RF-EMF exposure (Blettner et al 2008;Schreier et al 2006). This has pressured some countries (e.g., Switzerland and Belgium) to lower the precautionary regulatory exposure limits, whereas other countries (e.g., the Netherlands) retained exposure limits as proposed by the International Commission on Non-Ionizing Radiation Protection (ICNIRP).…”
Section: Introductionmentioning
confidence: 99%
“…Surveys using conventional psychological tests or questions with “yes” or “no” answers have been the most commonly used measures for the evaluation of effects of EMFs on health [Abdel‐Rassoul et al, 2007, Berg‐Beckhoff et al, 2009; Blettner et al, 2009]. However, investigations using conventional questionnaires failed to reveal any specific symptoms of EHS, nor clarified the severity of symptoms associated with exposure to specific EMF objects.…”
Section: Introductionmentioning
confidence: 99%
“…Blettner et al 19 found no association between living close to mobile phone base station and in-Cad. Saúde Pública, Rio de Janeiro, 31(10):1-16, out, 2015 creased cancer incidence, concluding that nonionizing electromagnetic radiation emissions were not related to adverse health outcomes.…”
Section: Introductionmentioning
confidence: 99%